Sedecimiella taiwanensis gen. et sp. nov., a marine mangrove fungus in the Hypocreales (Hypocreomycetidae, Ascomycota) - Pang, Ka-Lai; Alias, S.A.; Chiang, M.W.L.; Vrijmoed, L.L.P.; Jones, E.B.G. (Walter De Gruyter & Co, 2010)
In an ongoing survey of marine mangrove fungi in Taiwan, a fungus with light-coloured ascomata, resembling members of the Hypocreales, was found on twigs of Kandelia obovata. Based on morphological characteristics and partial nuclear small and large subunit ribosomal DNA data, the fungus is described as a new genus and species, Sedecimiella taiwanensis, and placed in the Hypocreales (Hypocreomycetidae, Ascomycota). Phylogenetic analyses based on LSU/SSU sequences did not resolve the familial placement of S. tawianensis within the Hypcreales, but it may be related to the Niessliaceae. The characteristic features of S. tawianensis are orange to dark-brown colour, soft-texture and perithecial ascomata with the inner wall layer of the neck extending into the upper part of the centrum; cylindrical, 16-spored, unitunicate asci without an apical pore; and hyaline, smooth-walled and globose ascospores.